Depth profiling of the microwave surface resistance of high-JC GdBa2Cu3O7−δ coated conductors grown using the RCE-DR process. (19th August 2016) - Yang, Woo II; Jung, Ho Sang; Lee, Jae-Hun; Lee, Hunju; Moon, Seung-Hyun; Lee, Jung-Woo; Yoo, Sang-Im; Lee, Sang Young
Abstract: We study depth profiling of the microwave surface resistance ( R S ) of GdBa2 Cu3 O7− δ (GdBCO) coated conductors (CCs) grown using the reactive co-evaporation by deposition and reaction (RCE-DR) method, a method enabling extremely high deposition rate. GdBCO CCs with the critical current ( I C ) of more than 790 A cm −1 at 77 K in self-field are used for the study. The R S of the GdBCO CCs is measured at temperatures of 10–80 K using a 8.5 GHz TE011 -mode rutile resonator, which is compared with that of YBa2 Cu3 O7− δ films and GdBCO films epitaxially grown on single crystal substrates. It turns out that there is significant inhomogeneity in the R S over the thickness of the GdBCO layer, with the R S value of the top part at 30 K being almost two times higher than the corresponding one of the bottom part. A transmission electron microscopy study reveals that Gd2 O3 grains coexist with GdBCO grains with the average Gd2 O3 grain sizes being ∼150 nm at the top and ∼100 nm at the bottom of the GdBCO layer. We relate the inhomogeneity in the R S of the GdBCO layer with the positional dependence of the Gd2 O3 grain size, for which effects of the dielectric losses from the Gd2 O3 grains on the measured R S of the GdBCO layer are considered. Our results imply that the critical current density, another important transport property of superconductors, could be inhomogeneous over the thickness of the GdBCO layer grown using the RCE-DR method.